ASSESSMENT OF KNOWLEDGE, ATTITUDE, AND PRACTICE REGARDING HYPOTHYROIDISM AMONG INFERTILE WOMEN WITH HYPOTHYROIDISM - PRASANNA G, VIMALA DEVA; SM, SHARUMATHI; SUNDARAM R, SHANMUGA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The study was designed to assess the knowledge, attitude, and practice (KAP) of hypothyroidism among infertile women with hypothyroidism. Methods: A cross-sectional analysis was performed in an outpatient environment of infertility centers. We used a validated questionnaire to assess hypothyroidism KAP. Using frequency counts (n) and percentages (%), discrete data were summarized. The Chi-square/Fisher test was used between groups to compare. Results: The mean age of participants was found to be 32±5.77 years. It was found that 72% of the subjects had poor knowledge, 44% were extremely concerned, and 81% were practicing with a moderate level of precaution. Among the consequences of hypothyroidism, 68% of the study subjects most properly-recognized menstrual disturbance, followed by 66%, 51%, and 48% of study subject properly-recognized weight gain, fatigue, and muscle aches/pain as a clinical manifestation of hypothyroidism. Most patients (98%) adhered to their medications. Nearly half of the study patients (45%) did not avoid cabbage, cauliflower, or soya. Conclusion: Our study highlighted the significance of investing appropriate time to provide patients with a comprehensive education to bridge the gaps in patient care. The findings also indicated that it be better for the understanding of the patients if health-care providers could provide patients with data sheets explaining the disease or having some pictorial/pamphlets about the disease’s reality and myths.